Being in the Batuecas: the making of a paradigm on peasantry in Early Modern Spain - Martín Marcos, David (Cuadernos de Historia Moderna, 2022)
The Batuecas Valley, and the region of Las Hurdes, was the place of a long-standing legend during the Early Modern Period; according to it, at the end of the 15th Century, some populations descent of the Goths and isolated during centuries would have been ‘discovered’ in their mountains. On this basis, this article analyses a paradigmatic formation of stereotype about the Spanish peasantry during the Ancien Régime. The work argues that, as it had happened in other rural areas, the supposed isolation of that territory gave rise to the creation of an imaginary in which the peasants were comparable to the indigenous population of America. Finally, it deals with the reasons for the fortune of this pseudo-historical cycle promoted by the theater of Lope de Vega and maps the frustrated attempts to cancel it.